Fine structure of the human hypoxanthine phosphoribosyltransferase gene. - Patel, P I (1986)
The human hypoxanthine phosphoribosyltransferase (HPRT) gene has been characterized by molecular cloning, mapping, and DNA sequencing techniques. The entire gene, which is about 44 kilobases in length, is composed of nine exon elements. The positions of the introns within the coding sequence are identical to those of the previously-characterized mouse HPRT gene, although there are significant differences between intron sizes for the two genes. HPRT minigenes have been used in a transient expression assay involving microinjection into HPRT- cells to demonstrate functional promoter activity within a 234-base-pair region upstream from the ATG codon. The promoter of this gene resembles those of other recently characterized "housekeeping" genes in that it lacks CAAT- and TATA-like sequences, but contains several copies of the sequence GGGCGG. Both RNase protection and primer extension analysis indicate that human HPRT mRNA is heterogeneous at the 5' terminus, with transcription initiation occurring at sites located congruent to 104 to congruent to 169 base pairs upstream from the ATG codon. Comparison of the mouse and human HPRT 5'-flanking sequences indicates that there are only limited stretches of conserved sequence, although there are other shared features, such as an extremely high density of potential methylation sites, that may have functional significance.